2014
DOI: 10.3233/wor-131671
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender normative data for lift capacity

Abstract: BACKGROUND: Functional Capacity Evaluations (FCEs) are routinely used in physical medicine to ascertain an individual's work ability; with lift capacity being an important aspect of many evaluations. Despite the widespread use of lift capacity tests, there are few studies that provide age and gender normative data. OBJECTIVE: To evaluate the safety, reliability, and validity of the EPIC Lift Capacity test, and to examine the effects of age and gender on lift capacity. METHODS: This study used a test-retest des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The exercise session included tasks that were chosen based on functional capacity assessments (e.g. Matheson's Group EPIC lift protocol), and in consultation with physiotherapists and occupational therapists (Matheson, 1993; Fisher & Jones, 2010; Oesch et al, 2015). The goal of the exercise session was to simulate the type of activity‐related pain that participants with low back pain may experience during their daily lives by performing everyday activities and movements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exercise session included tasks that were chosen based on functional capacity assessments (e.g. Matheson's Group EPIC lift protocol), and in consultation with physiotherapists and occupational therapists (Matheson, 1993; Fisher & Jones, 2010; Oesch et al, 2015). The goal of the exercise session was to simulate the type of activity‐related pain that participants with low back pain may experience during their daily lives by performing everyday activities and movements.…”
Section: Methodsmentioning
confidence: 99%
“…The piloting allowed for the tasks to be designed as highly feasible to ensure that all participants could complete the standardized exercise session and that it would evoke a range of pain responses among the clinical cohort. An RPE of eight or greater was used as a termination criteria for the exercise session (Matheson, 1993). Pilot data collected in our lab from participants with chronic low back pain indicated an RPE of 8/10 was tolerable and did not elicit any persisting negative symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Gender and age have a significant effect on lifting capacity (Matheson et al, 2014). Psychophysical rating of lift was found to be related to the strength and gender of the lifter (Jackson & Sekula, 1999).…”
Section: Proceedings Of the 2nd Indian International Conference On In...mentioning
confidence: 95%
“…Table -2 Lift Capacity :subset classification [5] Performance in the ELC subtests was studied in terms of both age and gender, the results of which are presented in Table 8. Main effects for both age group and gender are found for each of the subtests, (all p < 0.001).…”
Section: Comparison Of Load Impactmentioning
confidence: 99%
“…Main effects for both age group and gender are found for each of the subtests, (all p < 0.001). [5] An important use of the ELC data is to determine the adequacy of a person's lift capacity for his or her job's demands. And the values obtained from the above tabulation concluded that on an average, the liftable weight for an age group of (60+yrs) was found to be 23.78 kg and 15.76 kg for male and female gender respectively.…”
Section: Comparison Of Load Impactmentioning
confidence: 99%